High-flow Nasal Cannulae Versus Non-invasive Ventilation for Preoxygenation of Obese Patients: The PREOPTIPOP Randomized Trial. (August 2019) - Vourc'h, Mickael; Baud, Gabrielle; Feuillet, Fanny; Blanchard, Claire; Mirallie, Eric; Guitton, Christophe; Jaber, Samir; Asehnoune, Karim
Abstract: Background: In obese patients, preoxygenation with non-invasive ventilation (NIV) was reported to improve outcomes compared with facemask. In this setting, high-flow nasal cannulae (HFNC) used before and during intubation has never been studied against NIV. Methods: The PREOPTIPOP study is a randomised, single-centre, open-labelled, controlled trial including obese patients requiring intubation before scheduled surgery. Patients were randomised to receive preoxygenation by HFNC or NIV. HFNC was maintained throughout intubation whereas NIV was removed when apnea occurred to perform laryngoscopy. The study was designed to assess the superiority of HNFC. The primary outcome was the lowest level of end-tidal oxygen concentration (EtO2 ) within 2 min after intubation. Secondary outcomes included drop in pulse oximetry and complications related to intubation. Main findings: A total of 100 patients were randomised. The intent-to-treat analysis found median [IQR] lowest EtO2 of 76% [66–82] for HFNC and 88% [82–90] for NIV (mean difference − 12·1 [− 15·1 to − 8·5], p < 0·0001). Mild desaturation below 95% was more frequent with HFNC (30%) than with NIV (12%) (relative risk 2·5, IC 95% [1·1 to 5·9], p = 0·03) and median lowest SpO2 during intubation was 98% [93–99] in HFNC vs. 99% [97–100] in NIV (p = 0·03). Severe and moderate complications were not different but patients reported more discomfort with NIV (28%) vs. HFNC (4%), p = 0·001. Interpretation: Compared with NIV, preoxygenation with HFNC in obese patients provided lower EtO2 after intubation and a higher rate of desaturation < 95%. Funding: Institutional funding, additional grant from Fisher & Paykel. Trial Registration: Clinical trial Submission : April 10, 2017. Registry name : Preoxygenation Optimization in Obese Patients: High-flow Nasal Cannulae Oxygen Versus Non-invasive Ventilation: A Single-centre Randomised Controlled Study. The PREOPTIPOP Study. Clinicaltrials.gov identifier: NCT03106441 N°ID RCB: 2017-A00305–48. Institutional review Board : CPP Nord-Ouest I, registration number 019/2017. URL registry : https://clinicaltrials.gov/ct2/show/NCT03106441